Microstructure, microhardness, and wear performance of zirconia reinforced pure titanium composites prepared by selective laser melting. (14th December 2018) - Li, Jiangtao; Shen, Lida; Liu, Zhidong; Liang, Huixin; Li, Yize; Han, Xiao
Abstract: The study took selective laser melting (SLM) and strengthened pure titanium by adding zirconia particles in order to solve the low hardness, insufficient strength, and poor wear performance that pure titanium exhibits. The pure titanium's properties were improved by the strengthening and toughening properties of zirconia. In this study, the zirconia reinforced pure titanium composites were successfully prepared by SLM, and the weight fraction of zirconia was 3%. The phase, the microstructure, the microhardness, and the wear performance of the SLM-processed samples were studied. The results showed that the zirconia reinforcement phase with the fine structure was evenly distributed in the pure titanium matrix. Due to the fine grain strengthening and dispersion strengthening of zirconia particles, the microhardness of the SLM-processed zirconia reinforced pure titanium composites was significantly improved. When the laser linear energy density was 333.33 Jm −1, the microhardness of the sample with zirconia added was 426.51 ± 15.20 HV, which was almost double the pure titanium sample. In addition, the addition of zirconia powder resulted in a significant improvement in the wear performance of the SLM-processed sample compared to pure titanium.